Differential between multi-drug resistance pattern of extended spectrum b- Lactamases producing E. coli and K. pneumoniae - Ghafourian, Sobhan; Soheili, Sara; Aboualigalehdari, Elham; Sadeghifard, Nourkhoda; Mohebi, Reza; Maleki, Abbas; Awang Hamat, Rukman; Hosseini, Shiva; Sekawi, Zamberi (Oriental Scientific Publishing Company, 2014)
The current study aimed to determine the prevalence of Extended-Spectrum b-Lactamases (ESBLs) in Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) strains isolated from patients with Urinary Tract Infections (UTIs), to study the association between presence of ESBL enzyme and multi-drug resistance strains and finally, and to investigate the predominant ESBL gene in E. coli and K. pneumoniae. The strains were examined for the presence of ESBL as a Clinical Laboratory Standards Institute (CLSI) guideline. Among 284 clinical isolates, 52.8% (n = 150) and 47.2% (n =134) were E. coli and K. pneumoniae, respectively, and 110 strains were ESBL producer, which 68 strains were K. pneumoniae and 42 strains were E. coli. Significant difference observed between the TEM gene and ciprofloxacin resistant in E. coli (P ? 0.05) while no significant difference observed between CTX-M, SHV genes and the other multi-drug resistant E. coli. No significant difference observed between CTX-M, TEM, and SHV genes and multi-drug resistant K. pneumoniae. In conclusion, spreading of ESBL-producing strains is a concern, as it causes limitations to the antimicrobial agents for optimal treatment of patients. Prevalence of ESBLs was more observed in K. pneumoniae than E. coli. In addition, TEM gene was more prevalent in E. coli and resistance to ciprofloxacin was predominant in E. coli.